The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1155/2019/5431752
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Tissue Augmented with Deproteinized Bovine Bone Mineral Particles Associated with Implant Placement in Anterior Maxilla

Abstract: Background Implant placement in defective anterior maxilla poses a great challenge regarding functional and aesthetic outcomes. Therefore, it requires predictable alveolar ridge augmentation. Deproteinized bovine bone mineral (DBBM) particle has commonly been used for bone grafting. However, it is associated with low resorption rates which potentially compromise the outcome of horizontal augmentation in conjunction with implant placement. Aims This study is aimed at evaluating the stability of tissue augmented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…In a previous study, DBBMs showed a slow degradation rate and relatively low bone regeneration capacity [ 26 ]. Non-mineralized bone substitutes promote osteoblast differentiation by releasing bone morphogenic proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, DBBMs showed a slow degradation rate and relatively low bone regeneration capacity [ 26 ]. Non-mineralized bone substitutes promote osteoblast differentiation by releasing bone morphogenic proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoclasts could be associated with the resorption of the e quantification of protein expressions showed that osteoblastic markers were significantly higher in the DFDBBX group compared to the DBBM group (p < 0.05), except in ALP in 4 weeks (n � 5); * p < 0.05. 6 International Journal of Dentistry surrounding and the woven bone in the DFDBBX group during the late stage of healing. It is noteworthy, however, that the highest number of osteoclasts was seen in the control group indicating a consistent increase in resorption activities in 2 to 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…eir high osteoconductive activity allows cell migration, attachment, and proliferation, osteoblastic differentiation, and extracellular bone matrix deposition [5]. However, DBBM particles have a slow degradation rate and, consequently, relatively low bone regeneration capacity [6]. Demineralized freeze-dried bovine bone xenograft (DFDBBX) has been developed to overcome DBBM limitations [7].…”
Section: Introductionmentioning
confidence: 99%
“… 14 However, it was associated with very slow degradation that might lower its bone regeneration capacity. 4 In order to overcome DBBM limitation, mineralized FDBX and DFDBXs were developed recapitulating the concept and processing of human FDBA and DFDBA. 15 Despite the concern over the potential xenogeneic response upon its clinical application, this organic forms of xenograft material did not show abnormal immune response in few in vitro 7 16 17 18 and in vivo studies 7 9 19 as well as in a clinical study.…”
Section: Discussionmentioning
confidence: 99%
“…The DBBM particle is purely inorganic that is considered osteoconductive and exhibits extremely slow degradation which may reduce the bone regeneration capacity and bone-implant contact area. 4 5 Limitation of DBBM particle has made way to the utilization of other forms of bovine bone particles, that is, freeze-dried bovine bone particles (FDBX) and demineralized freeze-dried bovine bone particle (DFDBX) recapitulating the processing in allograft production. 6 Despite concerns over the potential xenogeneic response upon its application, these organic forms of xenograft material is proven to be nontoxic and nonimmunogenic in in vitro and in vivo studies.…”
Section: Introductionmentioning
confidence: 99%